Analysis of university students’ thinking skills - Shahzadi, Neelam; Buzdad, Muhammad Ayub (Journal of Pakistan Psychiatric Society, 2020)
Objective: This research investigates the prevalence of different thinking skills among the university students and find out the impact of gender difference on the thinking skills of university students.Design: It was descriptive study.Place and Duration:The study was conducted for a period of 1 year in different departments of GCWUF, GCUF and University of Agriculture, Faisalabad from 01-07-2016 to 30-06-2017.Subjects and Methods: The 670 students of different universities included in this sample. The rational experiential inventory (REI) and questionnaire of reflective thinking (QRT) were adapted to collect the required data. The questionnaire of reflective thinking measures the four dimensions are habitual action, understanding, reflection and critical reflection and the (REI) tools measured the rational and experiential thinking of university students.Results:  Findings of this study reveal that understanding of the university students’ is higher than the habitual action, reflection, and critical reflection. The rational thinking of university students is a more comprehensive than the experiential thinking of university students.Conclusion: To examine the thinking styles of the students, the review concludes that the presence of rational thinking is also higher than the experiential thinking among the university students included in the sample. However, the subscale wise comparison acknowledge that mean score of understanding is also higher than the other types of thinking skills.